Cavity ring-down spectroscopy of 17O-enriched water vapor between 12, 055 and 12, 260 cm−1. (December 2019) - Liu, A.-W.; Liu, G.-L.; Zhao, X.-Q.; Wang, J.; Tan, Y.; Hu, S.-M.
Highlights: More than 500 transitions assigned to 13 vibrational bands of H2 17 O. About 110 vibration-rotational energies of H2 17 O are newly obtained. The line positions were found to have significant discrepancies for more than 90 transitions of H2 16 O and H2 17 O in HITRAN2016 database. Abstract: The absorption spectrum of oxygen-17-enriched water vapor in the 12, 055–12, 260 cm −1 region was recorded with a continuous-wave cavity ring-down spectrometer (CW-CRDS) at room temperature. In total, 1342 lines were observed in this region, while more than 1400 absorption transitions were assigned based on previously published experimental energies and the variational calculations based on the results of Partridge and Schwenke. The typical frequency accuracy of 0.002 cm −1 was achieved in this work. Three hundred and fifty-eight ro-vibrational energy levels of H2 17 O water isotopologue were retrieved, which belong to the ν 1 + 1 2 ν 2 + ν 3 =3.5 and 4 polyads: (0 1 3), (0 3 2), (1 1 2), (1 3 1), (2 1 1), (2 2 1), (2 3 0), (3 0 1), and (3 1 0) states. One hundred and ten of them were reported for the first time. Comparisons of experimental line positions with those in the HITRAN database were given for H2 16 O and H2 17 O isotopologues. The obtained vibration-rotation energy levels were also compared with MARVEL values.